Ueber den Ort der Einstellungen im Satz Ueberlegungen im Grenzgebiet von Syntax und Pragmatik - Dippong, Horst (Specimina philologiae Slavicae, 1996)
The starting point of the work is an understanding of the theorem, also referring to Bachtin, as a "hybrid of sentence and utterance", of referential values ​​and pragmatic embedding. This is connected with the view that language knowledge is made up of autonomous, innate (partial) competencies. and acquired skills, and these interact with other knowledge systems. Consequently, the demand is raised for a linguistic paradigm that is capable of meaningfully integrating inherited and learned knowledge. The author sees his work as a first, "certainly quite bumpy attempt (...) in this direction". Thus, this work joins the current attempt to transgress the rigid limits of a too generatively understood generativistic. Horst Dippong accomplishes this in his own way with an original work, which can not be attributed to any single linguistic school, and which deserves an interested and critical reception.